Life’s Crucial 9 score and chronic kidney disease: insights from NHANES 2005–2018 and the mediating role of systemic inflammation and oxidative stress - Qin, Shiyuan; Yang, Jin; Wang, Zili; He, Pinglin; Dong, Taotao; Ren, Zhengyun; Li, Qiuyang (Frontiers in Medicine, 2025)
BackgroundChronic kidney disease (CKD) is a growing global health burden, closely linked to metabolic and cardiovascular risk factors. Life’s Crucial 9 (LC9) is a novel health assessment tool that expands upon Life’s Essential 8 (LE8) by incorporating mental health (depression) as a key component. This study aimed to investigate the association between LC9 and CKD, compare its predictive value with LE8, and explore potential mediating mechanisms.MethodsThis study analyzed data from 16,431 participants in the National Health and Nutrition Examination Survey (NHANES) 2005–2018. Logistic regression models were used to assess the association between LC9 and CKD, with comparisons to LE8. Restricted cubic spline models were applied to explore potential nonlinear relationships. Mediation analysis was conducted to evaluate whether systemic inflammation and oxidative stress mediated the association between LC9 and CKD. Receiver operating characteristic (ROC) analysis was performed to compare the predictive performance of LC9 and LE8 for CKD risk.ResultsHigher LC9 scores were significantly associated with a lower risk of CKD in both continuous and quartile-based analyses. A nonlinear relationship was observed between LC9 and CKD risk (P for nonlinearity < 0.001). Mediation analysis indicated that systemic immune-inflammation index (SII) and uric acid partially mediated the association between LC9 and CKD, with mediation proportions of 3.32 and 11.13%, respectively. ROC analysis showed that LC9 and LE8 had comparable predictive abilities for CKD.ConclusionHigher LC9 scores are associated with a reduced risk of CKD, with systemic inflammation and uric acid levels partially mediating this relationship. These findings highlight the importance of comprehensive lifestyle and mental health interventions in CKD prevention and management.